cDNA sequencing and expression analysis of Dicentrarchus labrax heme oxygenase-1 - Prevot-D'Alvise, N.; Pierre, S.; Gaillard, S.; Gouze, E.; Gouze, J. N.; Aubert, J.; Richard, S.; Grillasca, J. P. (Cellular and Molecular Biology, 2008)
The liver cDNA encoding heme oxygenase-1 (HO-1) was sequenced from European sea bass (Dicentrarchus labrax) (accession number no. EF139130). The HO-1 cDNA was 1250 bp in nucleotide length and the open reading frame encoded 277 amino acid residues. The deduced amino acid sequence of the European sea bass had 75% and 50% identity with the amino acid sequences of tetraodontiformes (Tetraodon nigroviridis and Takifugu rubripes) and human HO-1 proteins, respectively. A short hydrophobic transmembrane domain at the C-terminal region was found, and four histidine residues were highly conserved, including human his25 that is essential for HO catalytic activity. RT-PCR of mRNA from eight different European sea bass tissues revealed that, in a homeostatis state, the heme oxygenase-1 was abundant in the spleen and liver but not in the brain.